Die Hamburgisch-Lübischen Pfundgeldlisten 1485-1486 - Hormuth, Dennis; Jahnke, Carsten; Loebert, Sönke; der Freien und Hansestadt Hamburg, Staatsarchiv (Veröffentlichungen aus dem Staatsarchiv der Freien und Hansestadt Hamburg, 2006)
These two so-called "Pfundgeldlisten" are part of an eight-volume series. They record the income of a customs duty which was imposed to cover the costs of equipping peace ships and which was levied between 1480 and 1487 on entry and departure in the Port of Hamburg. These eight books of money are now in the archives of the Hanseatic city of Lübeck.